The Portrayal of Moral Particularism in Alcoholic Beverages Investment Policy - Utungga Pasopati, Rommel; Anadza, Hirshi; Syarifuddin, Syarifuddin (JASSP, 2022)
In the beginning of March 2021, President of Indonesia annulled alcoholic beverages investment policy which he put in decree about a week before. There were debates among experts and activists about how this investment should be done. Some believe that this decree may enhance local alcoholic beverages culture while others may reject it since the drinks are convinced to bring in bad effects to human beings. There are no universal moral statements, but particular ones, in this decree since people said in economic, cultural, and religious perspectives. Then, how may moral particularism be portrayed in alcoholic beverages investment policy in Indonesia? By examining concepts, theories, and written data, further analysis will be done to answer the question. Bureaucratic law, economic advantages, cultural indications, social impacts, and religious perspectives are the main tensions of this policy. Investment on alcoholic drinks as cultural indications may bring in economic advantages covered by bureaucratic law. However, any bureaucratic law will never omit possibilities of alcoholic abuse which will bring in negative impacts socially. Moreover, religious perspectives which are seen to be best guidance for people should be put above any law including prohibition of alcoholic drink. In conclusion, alcoholic beverages investment policy is the reflection of particularism rather than universal sights of moral conditions.